Function, mechanism of action, metabolism, and commercial application of Lonicera japonica: a review - Xinli Yang; Dan Yan (Food Science and Human Wellness)
Lonicera japonica (honeysuckle) is a traditional Chinese medicinal food, in which the main active ingredients are phenolic acids, polysaccharides, flavonoids, and volatile oils. They have various biological activities, including antiviral, antibacterial, antioxidant, hypoglycemic and lipid-lowering, and anti-inflammatory effects. This review summarizes the health effects and pharmacodynamic mechanisms of L. japonica extracts and the major active ingredients in these extracts, and the structures, metabolic process in vivo, and biotransformation processes of these compounds. In addition, the current status of the development of L. japonica-related functional foods is summarized. The aim is to provide a theoretical basis and reference for the further development and use of the active ingredients in L. japonica as functional foods for disease prevention and treatment.